Demographic and socio-economic factors affecting bed net ownership, usage, and malaria transmission among adult patients seeking healthcare in two Ghanaian urban cities - Ellis Kobina Paintsil; Enoch Boadi; Anthony Dwamena; Bless Hayford Addo; Agyei Kumi; Kwasi Obiri-Danso; Linda Aurelia Ofori (BMC, 2024)
Abstract Background The most cost-effective malaria prevention and control strategy is the use of a bed net. However, several factors affect the ownership and usage of bed nets among the adult population. Hence, this study aimed to examine socio-demographic factors affecting bed net ownership, usage and malaria transmission among adult patients seeking healthcare in two Ghanaian urban cities. Methods This hospital-based cross-sectional study was conducted, between January and September 2021, at Bremang Seventh-Day Adventist Hospital, Suame Municipal, Ashanti Region and Sunyani Municipal Hospital, Sunyani, Bono Region, Ghana. Structured questionnaires were administered to a total of 550 participants to ascertain their ownership and usage of the bed nets. Afterwards, finger prick blood samples were collected for malaria microscopy. Crude and adjusted prevalence ratios (PR) and their respective 95% CIs were calculated, using Poisson regression with robust standard errors, to show associated variables in bivariate and multivariate analyses respectively. R software (version 4.1.1) was used to perform all statistical analyses. Results About 53.3% (n = 293) of participants owned at least one-bed net but only 21.5% (n = 118) slept under it the previous night. Those married were 2.0 (95% CI: 1.6 - 2.5) and 2.4 (95% CI: 1.6 - 3.5) times more likely to own and use a bed net respectively than those who never married. Also, pregnant women were 1.3 (95% CI: 1.1 - 1.6) and 1.8 (95% CI: 1.3 - 2.5) times more likely to own and use a bed net respectively than non-pregnant. Even though income levels were not associated with bed net ownership and usage, students were 0.4 (95% CI: 0.2 - 0.6) and 0.2 (95% CI: 0.1 - 0.5) times less likely to own and use bed net respectively compared to formally employed persons. The overall malaria prevalence rate was 7.8%. Malaria-negative patients were 1.6 (95% CI: 1.2 - 2.0) and 2.4 (95% CI: 1.4 - 4.1) times more likely to own and use bed nets respectively than malaria positive. Patients with tertiary education recorded the lowest malaria prevalence (3.5%, n = 4). None of those with a monthly income > $300 recorded a case of malaria. On the contrary, majority 83%, n/N = 25/30) of the malaria-positive patients earned ≤ $150. Conclusion The National Malaria Control Program should conduct comprehensive mapping of all urban population segments before launching mass bed net distribution campaigns, taking into account demographic and socioeconomic factors to enhance bed net utilization and reduce malaria prevalence.